DISTRIBUTION ANALYSIS ANDMARKETING EFFICIENCY OF SEA FISH IN BANGLIAO OKI SINABOI SUB DISTRICTSINABOIROKAN HILIR REGENCY OF RIAU PROVINCE - J.M. Debataraja, Rivai; Yulinda, Eni; Arief, Hazmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbsrtakThis study aims to analyze the form of distribution channel involved in marketing fresh marine fish at Bangliao Oki, Sinaboi Sub District, Rokan Hilir Regwncy. Calculating marketing margins formed from the marketing of fresh marine fish at Bangliao Oki, Calculating the value of marketing efficiency at each marketing agency involved in the marketing process of fresh marine fish at Bangliao Oki Sinaboi Sub District Rokan Hilir Regency. The population in this study were the owner of Bangliao Oki, the fisherman who landed the fish in Bangliao Oki which amounted to 10 people, Agent which amounted to 2 people, 4 people along-along Traders, and 10 retailer merchants. The method used in this research is survey method by doing observation directly to the field (observation) By interviewing fishermen, Agent, retailer and other market players in Sinaboi Rokan Hilir Regency.The results of this study indicate that the pattern of distribution of fish commodities in Bangliao Oki found 2 (two) marketing channels, The most efficient marketing channel is the Marketing I channel involving Retailers, this is due to the marketing costs incurred and the selling price by smaller retailers rather than along-along. The two marketing channels in this study are efficient marketing, this is because the efficiency value is greater than 1 (one), the most efficient marketing is the marketing of the fish cencaru at the marketing institution along-along with the highest efficiency value that is 4.46 and the marketing with value the lowest efficiency is found in Agent marketing agency that is malong fish with efficiency value 2.08. Keywords:Bangliao Oki, Distribution, Marketing Margin, Marketing Efficiency